From Competency-Based to Merdeka Curriculum: A Comparative Study Based on Richards' Curriculum Development Theory - Muftihaturrahmah Burhamzah; La Sunra; Syarifuddin Dollah; Alamsyah Alamsyah; Sabrina Rocholl (Universitas Cokroaminoto Palopo, 2025)
This study presents a comparative analysis of Indonesia's Competency-Based Curriculum (CBC) and the newly implemented Merdeka Curriculum, utilizing Richards' curriculum development theory as a theoretical framework. Through document analysis, teacher interviews, and classroom observations across multiple Indonesian schools, this research examines both curricula across six key dimensions: goals, content, pedagogy, assessment, flexibility, and teacher autonomy. Findings reveal that while CBC emphasizes standardized competencies and measurable outcomes, the Merdeka Curriculum offers greater flexibility, student-centered approaches, and enhanced teacher autonomy. The transition reflects Indonesia's educational reform agenda to address 21st-century learning needs while respecting local contexts. Richards' framework proves particularly valuable in identifying systematic strengths and weaknesses in both approaches. The Merdeka Curriculum demonstrates significant potential for fostering creativity and critical thinking but faces implementation challenges related to resource distribution and teacher readiness. This study offers insights for policymakers, curriculum developers, and educational practitioners navigating curriculum reforms in similar contexts.